Criminal Liability Against Recidivists Abroad Who Recommit Crimes Theft in Indonesia - Dimas Aditya Nugraha (Institute Of computer Science (IOCS), 2022)
The theft of broken glass that occurred in the Province of the Bangka Belitung Islands, precisely in Tempilang Bangka Barat, Pal 9 Merawang, Bangka Regency and in front of My Snack Pangkalpinang City. Suspect E was convicted as a recidivist in Singapore. The purpose of this study is to determine the recidivist arrangements between the State of Indonesia and the State of Singapore and to determine the criminal liability of foreign recidivist Indonesian citizens who commit the crime of theft in Indonesia. The research method used is normative juridical with a statutory approach, a case approach and a comparative approach. The results of this study are that the recidivist arrangement in Indonesia is regulated in the general resident Article 486 of the Criminal Code, the punishment is plus 1/3 (one third) of the maximum criminal threat.